Increasing inclusions of Tribulus terrestris as an additive in diets of sheep kept in confinement - Y.S. Schunk; C.F.M. Mendes; R.A. T. Almeida; I.P. Raimundo; I.Q. Takahashi; C.F. Silva; R.L. Valença; R.O. Rego; L.C. Nunes; M.T.C. Almeida (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The aim was to evaluate the effects of increasing levels of Tribulus terrestris (TT) in diets of sheep in confinement on rumen parameters and blood metabolites. The experiment was conducted in two stages, in vitro, with inclusions ranging from 0 to 15.0 g/kg of TT in dry matter of the diet and the in vitro digestibility of dry matter and nutrients, pH, measurement of ammoniacal nitrogen and greenhouse gases were determined. And in situ, with inclusions of 0 to 5.0g/kg, in which five cannulated sheep were distributed in a 5 × 5 Latin square design to evaluate fermentation parameters, protozoan populations and blood metabolic profile. The inclusion of TT, regardless of dosage, resulted in decrease on in vitro digestibility, with quadratic effect on dry matter and nutrients, and reduction in ammoniacal nitrogen and methane. In terms of fermentation parameters, the safest dosages in vitro were 1.25 and 2.5g/kg. Inclusion of up to 5.0g/kg did not affect fermentation parameters in situ, did not harm the blood metabolic profile and reduced the population of small protozoa. Studies with inclusions greater than 5.0g/kg should be carried out to confirm the effect on protozoa, with subsequent analysis of production performance.